ANALISIS STRATEGI PT BUMYANG GLOVE DI YOGYAKARTA DALAM PENINGKATAN DAYA SAING - Emma Widianti; Nur hayati, Esti (Fakultas Ekonomi, Bisnis dan Humaniora, 2024)
PT Bumyang Glove Prime was established in 2021, with its main product being golf gloves. The company produces and distributes more than 10 types of gloves, including golf gloves, hiking gloves, riding gloves, and winter gloves. This research aims to analyze the strategies adopted by PT Bumyang Glove in Yogyakarta to enhance the company's competitiveness in the glove industry. The research method used is a qualitative approach with SWOT analysis, considering internal and external factors affecting the company. Data were obtained through interviews, field observations, and analysis of relevant documents. The results show that PT Bumyang Glove has successfully strengthened its position in the market through product diversification strategies, improving production quality, and investing in research and development. The company is also active in expanding its distribution network and forming partnerships with suppliers and potential customers. However, challenges such as intense competition, fluctuations in raw material prices, and changes in product quality standard regulations are also identified.